UPAYA PENINGKATAN KESEHATAN MASYARAKAT MELALUI EDUKASI DAN SKRINING PENYAKIT TIDAK MENULAR DI DESA MONGOLATO, KECAMATAN TELAGA - Waluyo, Darmayanti; Kaharu, Rosdiana; Rahmah, St. Mutiatu; Maesarah, Maesarah; Adam, Deysi; Hatta, Herman; Handayani, Lilis; Ntobuo, Fadillah Aulia; Modanggu, Tirsa; Beu, Sriwahyuni; Mohammad, Inggrid Anggraini A.; Tondako, Inka Noverita (Universitas Gorontalo, 2025)
This community service activity aims to improve the understanding of the Mongolato Village community regarding Non-Communicable Diseases (NCDs), such as hypertension and diabetes mellitus. The implementation was carried out through health education and screening of blood pressure and blood sugar levels in 100 respondents. The method used included a pretest-posttest to evaluate the respondents' understanding before and after education. The results showed an increase in community understanding by 20%, from an initial value of 59% to 79%. In addition, screening showed that 60% of respondents had high blood pressure, and 27% had high blood sugar levels. Education has proven effective in increasing public awareness of risk factors, prevention, and management of NCDs. As a follow-up, it is recommended to carry out routine monitoring and form health-conscious community groups to support sustainable prevention programs. Keywords: : Health education, Non-Communicable Diseases, screening, hypertension, diabetes mellitus.